Smoking Cessation Support Among Oncology Practitioners in a Regional Cancer Center in the Middle East—Improving a Critical Service for Cancer Care. (9th March 2016) - Obeidat, Nour A.; Ayub, Hiba S.; Amarin, Rula; Aburajab Altamimi, Barakat; Ghonimat, Iyad; Abughosh, Susan; Hawari, Feras I.
Abstract : This study examined smoking cessation support (SCS) by oncologists in a Jordanian cancer center and found it to be deficient. Recommendations to improve SCS include improving patient-provider communication and building providers' self-efficacy through continuing education.